2011
DOI: 10.4028/www.scientific.net/amr.347-353.444
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Efficiency of Environmental Pollution Control in Hebei Province Based on DEA Model

Abstract: DEA technique is widely used for efficiency evaluation of Decision Making Unit (DMU) with multiple inputs and outputs. This paper applies DEA model to the study of the efficiency of environmental pollution treatment in 8 provinces including Hebei and neighboring or Maritime Provinces. The results show that the efficiency of Efficiency of Environmental Pollution Control in Hebei Province is not high. Environmental pollution improvement in Hebei Province still needs to be expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Some scholars have paid attention to the second stage of environmental efficiency-that is, the efficiency of environmental governance. Ji et al (2011) used DEA to study the environmental governance efficiency of Hebei and eight surrounding coastal provinces. Their results showed that the environmental governance efficiency of Hebei is not high, and environmental pollution control still needs to be further strengthened.…”
Section: Environmental Efficiencymentioning
confidence: 99%
“…Some scholars have paid attention to the second stage of environmental efficiency-that is, the efficiency of environmental governance. Ji et al (2011) used DEA to study the environmental governance efficiency of Hebei and eight surrounding coastal provinces. Their results showed that the environmental governance efficiency of Hebei is not high, and environmental pollution control still needs to be further strengthened.…”
Section: Environmental Efficiencymentioning
confidence: 99%